Patterns in the Management of Endometriosis Among Physicians: A Cross-Sectional Survey [28A]. (May 2020) - Reddy, Srinidhi; McLaughlin, Jessica; Stansbury, Nicholas; Knudtson, Jennifer
Abstract : INTRODUCTION: Management of endometriosis is complex and varies among providers. This study investigates patterns in the management of endometriosis among Obstetrics and Gynecology physicians in the United States. METHODS: The Institutional Review Board reviewed and approved this study. A national online survey was sent to 5000 members of the American College of Obstetrics and Gynecology. It included 22 questions designed to assess the medical, surgical, and pain management of endometriosis. Variations in management were assessed using Fisher exact test and Mann-Whitney test. RESULTS: The adjusted response rate was 24.5%. The most common initial treatment for pelvic pain and suspected endometriosis was continuous combined oral contraceptives (COCs) (58%). When medical management fails, 52% of respondents opt for surgical management; 45% of respondents treat with excision while 42% treat with cautery ablation. Most indicated they offer postoperative hormone suppression, including continuous COCs (45%) or gonadotropin-releasing hormone agonists with add-back therapy (27%). The majority prescribe nonsteroidal anti-inflammatory drugs to treat endometriosis-related pain while a minority opt for alternative treatments such as opioids, acupuncture, and psychological support. 82% of physicians believe there is a need for women with endometriosis to have psychosocial care; however, only 15% routinely refer patients for psychological counseling. Importantly, 72% of respondents indicated they do not feel adequately trained to provide care for psychosocial aspects of endometriosis. CONCLUSION: The majority of responding providers are practicing evidence-based care for the treatment of endometriosis. Although most physicians recognize the need for a multidisciplinary approach to the treatment of endometriosis-related pain, only a minority recommend alternative treatments.